2001
DOI: 10.1034/j.1399-3011.2001.10972.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing heterodimeric two‐stranded α‐helical coiled‐coils: the effect of chain length on protein folding, stability and specificity

Abstract: The E/K coil, a heterodimeric coiled-coil, has been designed as a universal peptide capture and delivery system for use in applications such as biosensors and affinity chromatography. In this design, heterodimer formation is specified through the placement of charged residues at the e and g positions of the heptad repeat. The affinity and stability of the E/K coil has been modified in order to allow a greater range of conditions for association and dissociation by varying the chain length to obtain three, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
181
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(189 citation statements)
references
References 76 publications
8
181
0
Order By: Relevance
“…We chose the second model since sedimentation equilibrium experiments have shown that E5/K5 can form a tetramer with a dissociation constant (K d dimer-tetramer ) equal to 200 µM (22). Additionally, the observed molecular weight in sedimentation equilibrium experiments of E4/K4 was midway between that of the dimeric and tetrameric species, indicative of a dimertetramer equilibrium at high concentrations (23). An interaction between two EK dimers within the matrix of the biosensor is theoretically possible since the dextran chains have been shown to be flexible enough to allow for such an interaction (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the second model since sedimentation equilibrium experiments have shown that E5/K5 can form a tetramer with a dissociation constant (K d dimer-tetramer ) equal to 200 µM (22). Additionally, the observed molecular weight in sedimentation equilibrium experiments of E4/K4 was midway between that of the dimeric and tetrameric species, indicative of a dimertetramer equilibrium at high concentrations (23). An interaction between two EK dimers within the matrix of the biosensor is theoretically possible since the dextran chains have been shown to be flexible enough to allow for such an interaction (60).…”
Section: Discussionmentioning
confidence: 99%
“…The stability and affinity of this E/K system have been successfully modified by varying the R-helical propensity (serine vs alanine), the hydrophobicity of residues in the coiled-coil core (valine vs isoleucine), and the chain length (three to five heptads, or 21 to 35 residues) (23,24).…”
mentioning
confidence: 99%
“…These rules have been validated by database studies, 10,14 and are used as the cornerstone of much coiled-coil design. 2,[15][16][17] In addition, charged residues at e and g, which flank the hydrophobic core, Figure 1C&D, often form salt bridges in natural systems. 2,16,18,19 This is also exploited in coiled-coil design: judicious placement of complementary charges-e.g., Lys-Glu pairs at e and g-can be used to pattern sequences to control homotypic or heterotypic assembly of peptides otherwise possessing the same core a & d residues.…”
Section: Introductionmentioning
confidence: 99%
“…From the small size of a coiledcoil tag, we hypothesize that steric hindrance effects within the heterodimer would also be minimized when fused to a weakly interacting protein pair. In this work, we have used a coiled-coil pair (E3/K3) 11,12,17 as a tag to heterodimerize the two GFP variants ECFP and Venus, purified the heterodimer by a two-step affinity chromatography to homogeneity, and analyzed the E3/K3 interaction. The E3/K3 pair has the advantages of being short (21 amino acids per tag) and behaving as a heterodimer when the free peptides are analyzed in solution.…”
Section: Introductionmentioning
confidence: 99%
“…the past; 2,9-15 for example, properties like the association constant, specificity, and oligomerization state of interacting peptides in solution could be controlled to some extent. 12,16 A synthetic, de novo designed coiled-coil offers the possibility of specifically copurifying weakly interacting proteins that otherwise would not withstand conventional purification procedures and to analyze their interaction in vitro, even at low concentration. From the small size of a coiledcoil tag, we hypothesize that steric hindrance effects within the heterodimer would also be minimized when fused to a weakly interacting protein pair.…”
Section: Introductionmentioning
confidence: 99%